Cryptosporidium meleagridis infection: the first report in Poland of its occurrence in an HIV-positive woman - Wesołowska, Maria; Szostakowska, Beata; Kicia, Marta; Sak, Bohumil; Kvac, Martin; Knysz, Brygida (Annals of parasitology, 2016)
Cryptosporidium is an opportunistic protozoan parasite that can cause severe diarrhoea in immunocompromised patients. The transmission of this pathogen in humans and animals is not fully understood. C. meleagridis, originally described in birds, is the only Cryptosporidium species known to naturally infect mammalian and avian species. This study documents the first detection of C. meleagridis in an HIV-infected woman in Poland.
Keywords: AIDS; fatální výsledek; Cryptosporidium meleagridis; feces; Humans; Cryptosporidiosis; Anti-HIV Agents; kryptosporidióza; opportunistic parasites; HIV infekce; HIV Infections; Female; Polsko; dospělí; AIDS-Related Opportunistic Infections; Cryptosporidium; lidé; Poland; Feces; Adult; ženské pohlaví; HIV; oportunní infekce doprovázející AIDS; látky proti HIV; immunocompromised patients; Fatal Outcome